Salmonella enterica serovars in absence of ttrA and pduA genes enhance the cell immune response during chick infections - Julia M. Cabrera; Mauro M. S. Saraiva; Lucas B. Rodrigues Alves; Daniel F. M. Monte; Rosemeri O. Vasconcelos; Oliveiro C. Freitas Neto; Angelo Berchieri Junior (Scientific Reports, 2023)
Abstract Salmonella spp. is one of the major foodborne pathogens responsible for causing economic losses to the poultry industry and bringing consequences for public health as well. Both the pathogen survival ability in the intestinal environment during inflammation as well as their relationship with the host immune system, play a key role during infections in poultry. The objective of this study was to quantify the presence of the macrophages and CD4+/CD8+ cells populations using the immunohistochemistry technique, in commercial lineages of chickens experimentally infected by wild-type and mutant strains of Salmonella Enteritidis and Salmonella Typhimurium lacking ttrA and pduA genes. Salmonella Enteritidis ∆ttrA∆pduA triggered a higher percentage of the stained area than the wild-type, with exception of light laying hens. Salmonella Typhimurium wild-type strain and Salmonella Typhimurium ∆ttrA∆pduA infections lead to a similar pattern in which, at 1 and 14 dpi, the caecal tonsils and ileum of birds showed a more expressive stained area compared to 3 and 7 dpi. In all lineages studied, prominent infiltration of macrophages in comparison with CD4+ and CD8+ cells was observed. Overall, animals infected by the mutant strain displayed a positively stained area higher than the wild-type. Deletions in both ttrA and pduA genes resulted in a more intense infiltration of macrophages and CD4+ and CD8+ cells in the host birds, suggesting no pathogen attenuation, even in different strains of Salmonella.